LEARNERS STRATEGIES IN LEARNING ENGLISH PRONUNCIATION - Mursidah Rahmah; Abdul Rosyid (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2018)
The purpose of this research is to investigate the strategies applied by the learners in learning English pronunciation. This research attempts to answer the following research questions: (1) what are the strategies applied by the learners in learning English pronunciation? (2) What is the impact of the strategies applied by the learners toward their achievement in learning pronunciation? The participants of this study are 30 students who are still in the second semester in English Education Study Program, Pakuan University. The data were collected through classroom observation, questionnaire, and documentation in a form of audio recording, and in-depth interview with six representative participants. The major findings of this study are: (1) the strategies applied by the participants of this study are based on the strategies proposed by Calka (2001). From six strategies, cognitive strategy is the strategy whose the tactics mostly applied by the participants. (2) There is a good impact of pronunciation strategies toward pronunciation learning. The impacts are in a form of facilitating the process of learning and developing pronunciation ability and achievement.Keywords: EFL, Case Study, Pronunciation Learning StrategiesABSTRAKStrategi Pembelajar Bahasa Inggris dalam mempelajari Pronunciation Bahasa Inggris. Studi Kasus di Program Studi Pendidikan Bahasa Inggris, Universitas Pakuan. Tujuan penelitian ini adalah untuk menginvestigasi strategi yang diterapkan oleh pembelajar bahasa Inggris dalam mempelajari pronunciation Bahasa Inggris. Penelitian ini difokuskan untuk menjawab pertanyaan; (1) Apakah strategi yang diterapkan oleh pembelajar dalam memepelajari pronunciation bahasa Inggris? (2) Apakah dampak dari penerapan strategi belajar terhadap pembelajaran dan kemampuan pronunciation? Partisipan dalam penelitian ini adalah 30 mahasiswa semester 2 Program Studi Pendidikan Bahasa Inggris Universitas Pakuan.Pengumpulan data dilakukan dengan cara observasi dalam kelas, kuesioner, dokumentasi berupa rekaman suara partisipan saat membaca kata dan kalimat, serta interview perwakilan dari partisipan. Temuan dari penelitian ini antara lain; (1) Strategi yang diterapkan oleh partisipan adalah strategi yang disusun oleh Calka (2001). Dari enam strategi, kognitif strategi adalah strategi yang taktiknya paling banyak diterapkan oleh partisipan. (2) Ada dampak yang sangat baik dari penerapan strategi pembelajaran pronunciation terhadap kemampuan pronunciation. Dampak tersebut juga terlihat dari proses pembelajaran yang menjadi lebih mudah. Kata Kunci; EFL, Studi Kasus, Strategi Pembelajaran Pronunciation